Perancangan Produk Fashion Kontemporer Berdasarkan Budaya Peranakan Dengan Menerapkan Motif Batik Pesisir - Enrico (JURNAL RUPA, 2023)
Fashion industry in Indonesia has been growing tremendously by adaptng the archipelago’s culture as its unique identty. Peranakan as a result of acculturaton of local culture with that of China and Dutch which is infused with myriads of aesthetc values. This design is a representaton of cultural transformaton that stll holds the Peranakan identty while looking to ft into the target market as well as the current trend. This is done by way of qualitatve approach by accumulatng primary data through observaton, experiment and also secondary data via literature study. FRANGIPANI design method has 6 stages from searching for inspiraton to realizing the product and trialing it to the public. The purpose of this research is to introduce, promote and preserve the Peranakan culture as a fashion product that can be accepted by the current market. We hope this research will be one of the solutons for the Indonesian fashion industry and players to further develop products with Indonesian culture.